Tsenguluso nga ha thuthuwedzo i bveledzwaho nga kushumiselwe kwa thekhinolodzhi kha Tshivenda - Makumbane, Livhuwani Meriam (University of Limpopo, 2014)
The research focused on the effects of technology on language, with special reference to Tshivenda. These effects pertain to various aspects such as communication, agriculture, socialization, health, arts, sports, initiation schools, economy, transport, beliefs, food, drinks and utensils. The study further revealed that technology has several positive results such as the creation of new words. The study also indicated the negative effects of technology on language. In this regard it concentrated on the diminishing of Tshivenḓa words which ultimately may in future lead to their extinction. Lastly the study urged all people to accept technology and used in wisely for the benefit of our future generation because it is here to stay.
Thesis (M. A.) --University of Limpopo, 2014
Keywords: Technology; Language; Venda language; Communication and technology; Venda language - Technical Venda